THE INFLUENCE OF MOTIVATION AND WORK DISCIPLINE IN THE FRAMEWORK OF ISLAMIC ECONOMIC EMPOWERMENT ON THE PERFORMANCE OF COMPANY EMPLOYEES - Kaipa, Muhammad Akmal; Rachman, Muhamad Emil (Ijtimaiyya: Jurnal Pengembangan Masyarakat Islam, 2024)
In the era of globalization and increasingly fierce competition, companies are required to improve the performance of their employees to survive and thrive. PT. Pegadaian (Persero), one of the largest financial companies in Indonesia, faces similar challenges in its efforts to maintain a strategic position in the market. One strategy that can be used to improve employee performance is through increased motivation and work discipline. This study aims to analyze the effect of Work Motivation, Work Discipline, and Employee Performance at PT. Pegadaian (Persero) Kedaton Branch Bandar Lampung, a saturated sample was used to select 40 employees of PT. Pegadaian Kedaton branch. The analysis method uses multiple linear regression models, the coefficient of determination then hypothesis testing using the t-test and F test. The results showed that the t-test (partial) stated that work motivation had a positive and significant effect on the performance of PT. Pegadaian Kedaton employees, work discipline did not affect work productivity. While the F test has simultaneous results that work motivation and work discipline, significantly affect employee work productivity. The coefficient of determination analysis explains that motivation, discipline, and performance affect work productivity. this research not only has a direct impact on improving the performance of PT. Pegadaian (Persero) employees also make a significant contribution to the overall development of Islamic society. The application of the results of this study can be a catalyst for positive change in the business world and society, making Islamic values a strong foundation for sustainable and meaningful economic development.